The Effect of Health Education on Hygiene During Menstruation and Personal Hygiene of Santriwati (Female Student) at Boarding School - Arifa Retnowuni; Shrimarti Rukmini Devy; Rika Subarniati Triyoga (Humanistic Network for Science and Technology (HNST), 2017)
Islamic boarding school (Pesantren) as educational institutions have problems about personal hygiene and hygiene during menstruation. Therefore, it is necessary to have health education programs to change personal hygiene behaviour and hygiene during menstruation which aim at improving the female students health status. This research aims at analyzing the influence of health education on female students behavior about personal hygiene and hygiene during menstruation at Dormitory X Darul 'Ulum Pondok Pesantren Darul Ulum Jombang. The research design used SOR theory (Organism-Stimulus-Response). Stimulus is giving intervention health education which includes personal hygiene and hygiene during menstruation. The research method used lectures with a slides and booklets aid. Pretest was conducted before the treatment and posttest was conducted after 3 times the interventions. The subject of the research was female students of dormitory X Pondok Pesantren Darul Ulum Jombang. Expected response of this research is change knowledge, attitude and practice of personal hygiene and hygiene during menstruation. The result can be said that health education significantly affects their knowledge, attitude, and practice regarding personal hygiene. It also significanly affects their knowledge, attitude, and practice of hygiene during menstruation. Keywords: Health Education, Personal Hygiene, Hygiene during menstruation, Islamic Boarding School